Education the whole brain in an age of information technology: The English teacher as a "Brain Surgeon" - Abdul Rahman, Azly (Universiti Utara Malaysia, 1995)
Future shock - the disease of change - can be prevented. But it will take drastic social, even political action. No matter how individuals try to pace their lives, no matter what psychic crutches we offer them, no matter how we alter education, the society as a whole will still be caught on a runaway treadmill until we capture control of the accelerated thrust itself.Alvin Toffler, Future Shock (1970). Already we have fallen under its dominion. The year 2000 is operating like a powerful magnet on humanity, reaching down into the 1990s and intensifying change, heightening awareness, and compelling us to reexamine ourselves, our values and our institutions. John Naisbitt, Megatrebds 2000 (1990). A spectare is haunting the world view of teaching and learning as we approach the next millennium. Within the last few decades, we have witnessed a major advance in the field of cognitive psychology in which there is rapidly growing body of literature which there is rapidly growing body of literature which attempts to further conceptualize the working of the three pound human brain as more than a computer. Research in the field of neuroscience, cognitive psychology, and of late, in the field of classroom management are all pointing in the direction of synthesis with the rapid fission of " sociology of the future"; a novel field which attempts to describe the manner in which the human species will continue to survive in this age of "complexity and chaos". The purpose of this paper is to invite future educational policymakers, curriculum strategists, in general, and administrators and educators specifically to begin thinking about the cognitive processes involved in educating the human mind. Specifically, this paper, is an invitation for the teachers of English to become "brain surgeons" who will take into consideration the complex inner workings of the human mind and consequently engineer a progressive change as we enter another paradigm shift in the teaching of English. As this paper describes the "shape of things to come", it rests upon the following assumptions that: i. the survival of English Language Teaching is contingent upon the multitude of features characteristic of what is currently hailed as "The Decade of the Brain". "Survival" here means "the ability of the system to sustain cognitively" given a progressive diet of higher cognitive skills. ii. the nature of learning and teaching is inherently that of change. The way knowledge is viewed has always been constantly changing and as we approach the twenty-first century, change is all the more rapid and violent. Thus, the teaching of English must also be oriented towards change. iii. the maxim "Knowledge is Power" coined by the British philosopher Sir Francis Bacon is all the more true in this age of ultra sophistication in information technology. The approach towards acquiring, managing, and disseminating knowledge must be treated more systematically and effectively in order to treat knowledge as a resource of power. iv. the teaching of English albeit infused with the rhetoric's of English albeit infused with the rhetoric's of excellence as well as with an array of programmes for reform, may not effectively produce the greatest number of young intellectual elites who will be anable to cope with or bring about change in the next millennium. In other words, our school system is not yet a conductive breeding ground for future strategic and creative thinkers. Based on the above assumptions which are by no means exhaustive, I shall first discuss them as they relate to teaching of English. The second part of this paper will outline several philosophical and pedagogical considerations which can be made in order to sustain the progressiveness of the means and methods of teaching English. In short, this paper is titled "Educating the Whole Brain in an Age of Information Technology: The English Teacher as A 'Brain Surgeon' for the prime reason that the thinking of this new age revolves around the nation that in order to progress one needs to understand the nature of brain-based learning in the teaching of English and consequently engineer a paradigm shift in our system so that we will be ready to face the challenges of the next century. The English Teacher hence needs not only to be equipped with the art and science of teaching but also with knowledge of the current trends in our understanding of the brain.